Cross-sectional analysis of ethnic differences in fall prevalence in urban dwellers aged 55 years and over in the Malaysian Elders Longitudinal Research study - Alex, Deepa; Khor, Hui Min; Chin, Ai-Vyrn; Hairi, Noran Naqiah; Othman, Sajaratulnisah; Khoo, Selina; Kamaruzzaman, Shahrul Bahyah; Tan, Maw Pin (BMJ Publishing Group, 2018)
Objectives Falls represent major health issues within the older population. In low/middle-income Asian countries, falls in older adults remain an area which has yet to be studied in detail. Using data from the Malaysian Elders Longitudinal Research (MELoR), we have estimated the prevalence of falls among older persons in an urban population, and performed ethnic comparisons in the prevalence of falls. Design Cross-sectional analysis was carried out using the first wave data from MELoR which is a longitudinal study. Setting Urban community dwellers in a middle-income South East Asian country. Participants 1565 participants aged ≥55 years were selected by simple random sampling from the electoral rolls of three parliamentary constituencies. Outcome measures Consenting participants from the MELoR study were asked the question € Have you fallen down in the past 12 months?' during their computer-assisted home-based interviews. Logistic regression analyses were conducted to compare the prevalence of falls among various ethnic groups. Results The overall estimated prevalence of falls for individuals aged 55 years and over adjusted to the population of Kuala Lumpur was 18.9%. The estimated prevalence of falls for the three ethnic populations of Malays, Chinese and Indian aged 55 years and over was 16.2%, 19.4% and 23.8%, respectively. Following adjustment for ethnic discrepancies in age, gender, marital status and education attainment, the Indian ethnicity remained an independent predictor of falls in our population (relative risk=1.45, 95% CI 1.08 to 1.85). Conclusion The prevalence of falls in this study is comparable to other previous Asian studies, but appears lower than Western studies. The predisposition of the Indian ethnic group to falls has not been previously reported. Further studies may be needed to elucidate the causes for the ethnic differences in fall prevalence.